Utilization of Listening Assistive Technologies and the Academic Performance in Primary Schools for Learners with Hearing Challenges in Meru and Tharaka Nithi Counties, Kenya - Murithi, Sabina; Mwirichia, Severina; Gichohi, Paul Maku (International Journal of Professional Practice, 2022)
The government of Kenya has established measures such as training and employment of teachers to deliver quality education to learners with hearing challenges. However, the academic performance in primary schools for learners with hearing impairments has been poor. This study investigated the effect of utilizing assistive technologies on the academic performance in primary schools for learners with hearing challenges in Meru and Tharaka Nithi counties, Kenya. It specifically examined the effect of listening assistive technologies on academic performance. It was guided by the capability theory. The three hearing-impaired special schools in Meru and Tharaka Nithi County were the study’s sample. There were 91 pupils, 13 teachers, and 9 technical support personnel. Three school principals and 2 County Educational Directors for Education were interviewed. The study used a cross-sectional survey. Questionnaires, interview guide, focused group discussion, and document analysis were utilized to collect data. Descriptive statistics and correlation were used to analyze quantitative data, while thematic technique was used on qualitative data. The findings were presented using tables, figures and identified themes. A pre-test was conducted to address the validity and reliability of the research instruments. The study discovered a positive link between the use of listening assistive devices and academic achievement in primary schools for students with hearing impairments. It also noted a low usage of listening assistive technologies, which was ascribed to listening assistive device inadequacy, a lack of skills for utilizing them, poor equipment maintenance, and a lack of appropriate support from schools, government, family, and the community. The Ministry of Education should develop a strategy to acquire all the necessary listening assistive technology equipment for students with hearing impairments in all primary schools. Head teachers were advised to develop training strategies for complicated listening assistive devices to reduce the rate of breakages and breakdowns.